2007
DOI: 10.1627/jpi.50.1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ultraviolet Absorbers on Decomposition of Hydroperoxide by Hindered Amine Light Stabilizers

Abstract: The interaction between hindered amine light stabilizers (HALS), and ultraviolet absorbers (UVA) was investigated, in order to clarify the reason why they generally show synergism, although UVA belong to kinds of phenols. A homolytic decomposition of cumene hydroperoxide (CHP) by amine-type HALS (HALS NH) in the presence of UVA is the antagonism bringing about autoxidation. This antagonism is found considerably weaker for UVA than that of 3,5-di-t-butyl-4-hydroxytoluene. This is based on a weak proton-donating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Interestingly, an equimolar mixture of UVA and HALS NH shows similar or greater photo-antioxidant activity compared with that of a double amount of only UVA 41) . This synergism is ascribable to the regeneration of UVA, because HALS has no particular photoantioxidant functions.…”
Section: 2 Synergistic Interaction Of Hals and Uvamentioning
confidence: 97%
“…Interestingly, an equimolar mixture of UVA and HALS NH shows similar or greater photo-antioxidant activity compared with that of a double amount of only UVA 41) . This synergism is ascribable to the regeneration of UVA, because HALS has no particular photoantioxidant functions.…”
Section: 2 Synergistic Interaction Of Hals and Uvamentioning
confidence: 97%
“…73 It is also considered, based on experimental data, that UV absorbers of benzophenone and benzotriazole types occasionally lose phenolic hydrogen during repeated UV absorption and they become quinoid compounds which do not participate in energy dissipation cycle. 74 HAS is thought to be able to reduce the quinoid structure to the regular phenolic form which can exhibit its normal UV absorption activity. 74 The combination Tinuvin 662 (polymeric HAS)/Chimassorb 81 (benzophenone) yields a quite pronounced synergism.…”
Section: Repairing Defects Caused By Degradationmentioning
confidence: 99%
“…74 HAS is thought to be able to reduce the quinoid structure to the regular phenolic form which can exhibit its normal UV absorption activity. 74 The combination Tinuvin 662 (polymeric HAS)/Chimassorb 81 (benzophenone) yields a quite pronounced synergism. In the presence of titanium dioxide, UVA no longer contributes to UV stability.…”
Section: Repairing Defects Caused By Degradationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these mechanisms do not seem to explain the synergism perfectly. On the other hand, the authors reported a good relationship between the inhibition of photooxidation by UVA and the initial rate of homolytic decomposition of a hydroperoxide by HALS in the presence of UVA, and concluded no or little antagonism of UVA with HALS 6) . In this study, we confi rm it experimentally and propose a new synergism of HALS and UVA by comparing the action of UVA (2-hydroxybenzophenone) with that of phenol (BHT) with respect to both antagonism and synergism with HALS.…”
Section: Introductionmentioning
confidence: 99%